Many waters - L'Engle, Madeleine (New York : Bantam Doubleday Dell Books for Young Readers, 1997)
The fifteen-year-old Murry twins, Sandy and Dennys, are accidentally sent back to a strange Biblical time period, in which mythical beasts roam the desert and a man named Noah is building a boat in preparation for a great flood.
"A Yearling book."
Companion to: A wrinkle in time.
Originally published: New York : Farrar, Straus, Giroux, 1986.
Keywords: Noah -- (Biblical figure) -- Fiction; Noah's ark -- Fiction; Twins -- Fiction; Time travel -- Fiction; Fantasy